Effects of Different Forms of Iron and Aluminum Oxides on Soil Organic Carbon Content Under Native Coniferous and Broadleaf Plantations in South Subtropical Region of China - Zhu Hao; Xiao Zhirou; Ming Angang; Teng Jinqian; Qin Lin (Shuitu baochi tongbao)
[Objective] The effects of different forms of iron and aluminum oxides on soil organic carbon content in native coniferous and broadleaf plantations in south subtropical region of China were studied in order to provide a scientific basis for further understanding the soil organic carbon accumulation mechanism of native tree plantations in this region. [Methods] The study was conducted in three native coniferous and broadleaf planted forests including a pure Pinus massoniana coniferous plantation, a pure Erythrophleum fordii broadleaf plantation, and a mixed plantation of these species located at the Experimental Center of Tropical Forestry, the Chinese Academy of Forestry, at Pingxiang City, Guangxi Autonomous Region. ICP-OES and the potassium dichromate method were respectively used to measure the content of iron and aluminum oxides and soil organic carbon content in different soil layers (0—20, 20—40, 40—60 cm) under each plantation. Analysis of variance was used to determine differences in observed indicators in different soil layers and stands. Pearson correlation analysis was used to test the relationship between different forms of iron and aluminum oxides and organic carbon. [Results] The content of soil organic carbon in the mixed plantation of P. massoniana and E. fordii was significantly greater than in the pure P. massoniana plantation and the pure E. fordii plantation, and the content of soil organic carbon decreased with increasing soil depth in the three plantations. Fed (total free mineral Fe oxides) was the highest of all forms of iron and aluminum oxides in the studied stands, followed by Ald (total free mineral Al oxides), Feo (non-crystalline mineral Fe oxides), Alo (non-crystalline mineral Al oxides), Fep (organic bounded mineral Fe oxides), and Alp (organic bounded mineral Al oxides). Furthermore, Fed and soil organic carbon had a significant negative correlation (p<0.05), while Feo, Fep, and Alp were positively and significantly correlated with soil organic carbon content (p<0.05). [Conclusion] Soil organic carbon mineralization was enhanced due to high levels of Fed under native coniferous and broadleaf plantations in south subtropical region of China. Although Feo, Fep, and Alp contents were low, they could increase soil organic carbon retention and stability.